Biomaterials Based on Organic Polymers and Layered Double Hydroxides Nanocomposites: Drug Delivery and Tissue Engineering - Vera Regina Leopoldo Constantino; Mariana Pires Figueiredo; Vagner Roberto Magri; Denise Eulálio; Vanessa Roberta Rodrigues Cunha; Ana Clecia Santos Alcântara; Gustavo Frigi Perotti (MDPI AG, 2023)
The development of biomaterials has a substantial role in pharmaceutical and medical strategies for the enhancement of life quality. This review work focused on versatile biomaterials based on nanocomposites comprising organic polymers and a class of layered inorganic nanoparticles, aiming for drug delivery (oral, transdermal, and ocular delivery) and tissue engineering (skin and bone therapies). Layered double hydroxides (LDHs) are 2D nanomaterials that can intercalate anionic bioactive species between the layers. The layers can hold metal cations that confer intrinsic biological activity to LDHs as well as biocompatibility. The intercalation of bioactive species between the layers allows the formation of drug delivery systems with elevated loading capacity and modified release profiles promoted by ion exchange and/or solubilization. The capacity of tissue integration, antigenicity, and stimulation of collagen formation, among other beneficial characteristics of LDH, have been observed by in vivo assays. The association between the properties of biocompatible polymers and LDH-drug nanohybrids produces multifunctional nanocomposites compatible with living matter. Such nanocomposites are stimuli-responsive, show appropriate mechanical properties, and can be prepared by creative methods that allow a fine-tuning of drug release. They are processed in the end form of films, beads, gels, monoliths etc., to reach orientated therapeutic applications. Several studies attest to the higher performance of polymer/LDH-drug nanocomposite compared to the LDH-drug hybrid or the free drug.